Morpho-syntactic concept and contribution of Tholkaappiyar : a view from a different prism - Muthusamy, Paramasivam; Hassan @ Hussin, Omrah; Pillai, N. Nadaraja; Muniandy, Rajantheran; Kandsamy, Silllalee S.; Subramaniam, Manimaran (PalArch Foundation, 2020)
The concept of morpho-syntax is defined as ‘the study of grammatical affixes or linguistic units that have both morphological and syntactic properties’. The author of Tholkaappiyam, the earliest written Tamil grammar of 300 B.C., explains this concept exhaustively in different chapters. This notion of modern Linguistics is to be added as one of the levels of language for research and teaching grammar as well. A per the author of the grammar, tense is a morpho-semantic feature, which is added to finite verbs. Tense marker attributes to the meaning of the sentence and not to the sentence structure. That was his concept and contribution to the field of Linguistics. Features like, metonymy, ambiguity, gerund formation, etc., in the grammar, support the concept proposed. Selected verses from Tholkaappiyam have been quoted for the sustenance of his view. Additionally, this article brings in another very important concept of ‘mid-fix’, which is a new contribution to the field.